2009
DOI: 10.1111/j.1600-0625.2008.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective photodynamic therapy of actinic keratoses on the head and face with a novel, self‐adhesive 5‐aminolaevulinic acid patch

Abstract: The results of this first clinical efficacy study suggest excellent therapeutic outcomes with a single PD P 506 A PDT with a 4-h application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…Four SCC cells lines have been used in this study as model for epithelial skin cancer, because of a general lack of AK cell lines. Furthermore, AK is frequently assessed as an early stage of invasive SCC (Quatresooz et al, 2008;Hauschild et al, 2009), and similar pathway aberrations have been reported in AK and SCC, particularly including the COX-2 pathway Muller-Decker and Furstenberger, 2007). The SCC cell lines investigated here have been used in many other laboratories and are generally accepted as representative for cutaneous skin cancer (Rheinwald and Beckett, 1981;Tilgen et al, 1983;Schon et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Four SCC cells lines have been used in this study as model for epithelial skin cancer, because of a general lack of AK cell lines. Furthermore, AK is frequently assessed as an early stage of invasive SCC (Quatresooz et al, 2008;Hauschild et al, 2009), and similar pathway aberrations have been reported in AK and SCC, particularly including the COX-2 pathway Muller-Decker and Furstenberger, 2007). The SCC cell lines investigated here have been used in many other laboratories and are generally accepted as representative for cutaneous skin cancer (Rheinwald and Beckett, 1981;Tilgen et al, 1983;Schon et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…AK lesions, which derive from neoplastic epidermal keratinocytes, are primarily restricted to the epidermis; however, they may proceed to invasive squamous cell carcinoma (SCC). Therefore, and due to histological and molecular correspondence, AK is considered by some researchers a carcinoma in situ and an early stage of invasive SCC (Quatresooz et al, 2008;Hauschild et al, 2009). Topical 3% diclofenac sodium in 2.5% hyaluronic acid solution (diclofenac/hyaluronic acid (HA), Solaraze) has been approved as a new treatment for AK and has shown significant efficacy (Merk, 2007;Stockfleth et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…One randomized controlled study found that complete clearance of actinic keratoses 8 weeks after treatment occurred with 4-hour incubation of the self-adhesive ALA patch (86% of actinic keratosis lesions) and red light therapy. Shorter incubation times at 2 hours (73%), one hour (72%), and half an hour (51%) proved to be subpar 59. In one Phase III study, the 5-ALA patch-PDT without crust removal proved superior (82% and 89%) to placebo-PDT (19% and 29%, P <0.001) and cryosurgery (77%) in improvement of actinic keratosis lesions on the scalp 60…”
Section: Pdt In Neoplastic Diseasementioning
confidence: 99%
“…PDT mit Methyl-aminolävulinsäure (MAL) und 5-Aminolävulinsäure (ALA) wurde als effektiv bei der Behandlung von AK und Feldkanzerisierung beurteilt [26,28,29]. Durch die Applikation photosensitivierender Stoffe wie 5-Aminolävulin-säure (5-ALA), einer physiologischen Vorstufe des Porphyrins, und nachfolgende Bestrahlung mit Licht geeigneter Wellenlänge werden reaktive Sauerstoffspezies (ROS) produziert, die primär zytotoxische Effekte induzieren [24].…”
Section: Introductionunclassified